Spenser at Play - Moshenska, J (Modern Language Association, 2019)
Reading The Faerie Queene is like playing. This article develops an account of three relevant tendencies of play—to change through time, to animate its object, and to remain opaque in meaning—and distinguishes this account from other critical understandings of play. It then introduces a historical analogue to Spenser’s playfulness—the giving of formerly holy objects to children as toys during the Reformation—and uses it as a lens through which to read the ending of the first book of Spenser’s poem, where the vast dragon not only becomes a posthumous plaything but also displays surprisingly playful propensities of its own. Readers respond both to this moment and to their own responses to it, playing in the presence of the poem’s opaquely foregrounded meanings. (JM)